2016
DOI: 10.1002/pat.3851
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of polyimide/chopped carbon fiber composite foams

Abstract: In this study, a series of reinforced polyimide (PI)/carbon fiber (CF) composite foams were fabricated through thermal foaming of polyester ammonium salt (PEAS) precursor powders. The PEAS precursor powders containing different contents of chopped CF were synthesized from benzophenone‐3,3′,4,4′‐tetracarboxylic dianhydride (BTDA) and 4,4′‐diaminodiphenyl ether (ODA). The effects of different CF loadings on foaming behavior of PEAS/CF composite precursor powders, final cellular morphology, and physical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 34 publications
(44 reference statements)
0
25
0
Order By: Relevance
“…The molecular structure of the used PAPI is shown in Scheme 1 (5). The molecular structure of the used PAPI is shown in Scheme 1 (5).…”
Section: Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular structure of the used PAPI is shown in Scheme 1 (5). The molecular structure of the used PAPI is shown in Scheme 1 (5).…”
Section: Preparationmentioning
confidence: 99%
“…The special rigid structure of imide rings provides numerous excellent properties to PI foams, including lightweight, flame retardant, thermal insulation, acoustic absorption, and wide operating temperature, which make PI foams possess wide applications in the fields of aerospace craft, airplane, marine, cars, and so on. [5][6][7] Compared with two-step method, one-pot method has a lot of advantages, such as simple production technology, efficient production cycle, and low cost, which is suitable for the preparation of low density PI foams. 4 For one-pot method, aromatic dianhydride and its derivatives react with polyaryl polymethylene isocyanate (PAPI), foaming with CO 2 produced by itself, and the foaming process is also impacted by various kinds of assistants together.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that adding nano-inorganic particles to a polymer as a heterogeneous nucleating agent can effectively improve the quality of the cell morphology, as well as the impact toughness and heat insulation performance of microfoaming materials [ 17 , 18 , 19 , 20 ]. However, the nucleation efficiency of nano-inorganic powders is reduced because of their high surface density and easy agglomeration [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the introduction of ESFs into CF nonwoven fabrics can admirably remedy the shortcomings of conventional polymer binders. Additionally, CFs and ESFs can both be applied to selected severe domains, such as fuel cells and lithium batteries, due to their good chemical resistance . In recent years, with the advent of portable and wearable electronics, such potential flexible‐structured conductive fabrics have gained promising application prospects.…”
Section: Introductionmentioning
confidence: 99%